Freudian theories of homosexual development: A basic overview - Phelan, James (Technium Social Sciences Journal, 2020)
Richard von Krafft-Ebing, Jean-Martin Charot, and Havelock Ellis were a few antecedents to Sigmund Freud in identifying, defining, and theorizing the development of homosexuality. However, the majority subscribed to the thought that homosexuality was congenital, albeit unnatural. Havelock Ellis offered some psychological considerations to the condition of homosexuality and was said to have paved the way for more significant developmental explanations that began with Freud. According to Caprio (1954) the congenital theories prior to Freud became “obsolete” (p. 3). Because of the contributions of Freud, psychoanalysts that followed him such as Sandor Rado, Edmund Bergler, Irving Bieber, Lionel Ovesey, and Charles Socarides, to name a few, took on views that homosexuality was developmental in nature. During the phallic phase of development Freud made a pivotal discovery about the oedipal complex. This and other theories of psychosexual development are overviewed. It is important to get an understanding of the basic construct of theory given the rise of deconstruction and reconstruction undertakings.